Commoners and Revolución Ciudadana: The cases of Otavalo and Cotacachi in Ecuador - Ortiz Crespo, Santiago (2013)
Since 2006 the indigenous political vote has split between Pachakutik and Alianza País (AP). The latter is a political movement led by Rafael Correa, currently president of Ecuador. The article seeks an explanation for this distribution of the vote, examining the political behavior of the indigenous people of the Otavalo and Cotacachico unties of the northern Ecuadorean highlands. It argues that the support for Correa can be explained by several factors: (1) the historical relationship between indigenous people and the State; (2) an electoral behaviour that combines trust in ethnic leaders and pragmatism; and (3) an expectation of «more state presence». The study is based on two surveys of leaders and local population, participant observation and interviews, as well as a document review.